Trends in nicotine yield in smoke and its relationship with design characteristics among popular US cigarette brands, 1997–2005. Issue 5 (26th September 2007) - Connolly, Gregory N; Alpert, Hillel R; Wayne, Geoffrey Ferris; Koh, Howard
Abstract : Objectives: To determine whether nicotine yields in the smoke of cigarettes would show an overall increase over time or an increasing trend limited to any particular market category (eg, full flavour vs light, medium (mild) or ultralight; mentholated vs non-mentholated), manufacturer, or brand family or brand style, and whether nicotine yields in smoke would be associated with measurable trends in cigarette design. Methods: Machine-based measures of nicotine yield in smoke and measures of cigarette design features related to nicotine delivery (ventilation, nicotine content in the tobacco rod and number of puffs), as well as market category descriptors, were obtained from annual reports filed with the Massachusetts Department of Public by tobacco manufacturers for 1997–2005. Trends in nicotine yield and its relationship with design features and market parameters were analysed with multilevel mixed-effects regression modelling procedures. Results: A statistically significant trend was confirmed in increased nicotine yield, of 0.019 (1.1%) mg/cig/year over the period 1997–2005 and 0.029 (1.6%) mg/cig/year over the period 1998–2005. The increasing trend was observed in all major market categories (mentholated vs non-mentholated, and full flavour vs light, medium (mild) or ultralight). Nicotine yield in smoke was positively associated with nicotine concentration in the tobacco and number of puffs per cigarette, both of which showed increasing trends during the study period. Conclusions: This study confirms increased machine-measured levels of nicotine, the addictive agent in cigarettes, in smoke, to be a result of increased nicotine in the tobacco rod and other design modifications.